The Rhetoric and Reality of Localisation: Refugee-Led Organisations in Humanitarian Governance. - Pincock, Kate; Betts, Alexander; Easton-Calabria, Evan (Journal of Development Studies, 2021)
When refugees flee war and persecution, protection and assistance are usually provided by United Nations organisations and their NGO implementing partners. In parallel is a largely neglected story: refugees themselves frequently mobilise to provide protection and assistance to other refugees. At a global level, there has been a shift in international policy rhetoric towards 'localisation' and inclusion of refugees, which potentially provides an opportunity to engage with refugee-led community organisations (RLOs). However, RLOs rarely receive access to international recognition or funding despite often being regarded by refugees as an important source of assistance. In this paper we draw upon ethnographic research on the interactions between international institutions and RLOs in Kampala, Uganda, to explore how 'localisation' unfolds in practice within humanitarian governance. In the absence of a clear policy framework for localisation at the global level, national level representatives have considerable discretion in whether and how they partner with RLOs, leading largely to their exclusion – and the development of alternative support strategies by RLOs. We suggest that an effective localisation agenda will require much more attention to the role of power and interests at the local level if RLOs are to be engaged as meaningful actors in humanitarian assistance.